FAKTOR-FAKTOR YANG MEMPENGARUHI KEDISIPLINAN BELAJAR SISWA KELAS V SDN 1 PELEMKEREP PADA MATA PELAJARAN PPKn - Novita Minggi; Ika Ari Pratiwi; Ahmad Bakhrudin (STKIP Subang, 2023)
Discipline has a great influence on the learning process. Studying with discipline can increase enthusiasm during the learning process. This study aims to analyze the factors that influence the learning discipline of fifth grade students at SDN 1 Pelemkerep in Civics learning subjects. This research uses a qualitative approach with descriptive methods. This research was conducted at SDN 1 Pelemkerep which is located in Pelemkerep Village, Mayong District, Jepara Regency in May 2023. The subjects in this study were a class V teacher and 6 class V students at SDN 1 Pelemkerep who were selected by researchers in the category of 2 students with a high level of learning discipline , 2 students with a low level of learning discipline, and 2 students who do not have a learning discipline. Data collection techniques used in this study through observation, interviews, and documentation. The data validation test in this study used the triangulation method. Data analysis techniques using data reduction, data presentation, and conclusions/verification. The results of this study are that the learning discipline of fifth grade students at SDN 1 Pelemkerep in Civics subjects is influenced by two factors, namely intrinsic factors and extrinsic factors. Intrinsic factors are factors that come from within students including: interest, motivation, and cognitive abilities. While extrinsic factors are factors that come from outside the students themselves including: school environment, family environment, and community environment.